Cross-Lingual Sentiment Analysis for Indonesian Monetary Policy - Akbar Ramadhan; Umar Zaky (Kirana Publisher (KNPub), 2025)
This research develops a cross-lingual sentiment analysis system (RoBERTa-IndoBERT) to monitor public opinion on Bank Indonesia’s 2025 monetary policy from X (Twitter), addressing the scarcity of Indonesian labels and noisy social media text. We introduce a